Assessing the knowledge of key one health elements among African higher education students: African multi- center cross-sectional study - Fatma A. Amer; Nkalubo Jonathan; Hana A. Nofal; Rehab Tash; Noha M. Hammad; Manar G. Gebriel; Elichilia Robert Shao; Ibrahim Eldaghayes; Djamila Meriane; Ayman A Allam; Heba Mohtady Ali; Raghda A. Hafez; et al. (BMC Public Health)
Abstract Background The One Health (OH) approach addresses the interconnectedness of human, animal, and environmental health, playing a critical role in tackling antimicrobial resistance (AMR), zoonotic diseases, and climate change. Despite its importance, limited research has examined OH knowledge among African students - future professionals in public health, veterinary science, and environmental fields. Objectives This study assesses OH knowledge and its key components - AMR, zoonosis, and climate change - among higher education students across 26 African countries. Methods A cross-sectional, multicentre study was conducted from June 2023 to February 2024, using an online survey distributed in English and French. The survey targeted higher education students from diverse academic disciplines. OH knowledge levels were evaluated based on median scores, and statistical analysis using Statistical Package for the Social Sciences (SPSS) software version 24 identified regional and disciplinary variations. Results A total of 726 students from 26 African Countries participated in the study. 88.2% of Central African students demonstrated adequate OH knowledge, while students from North Africa exhibited the lowest scores (64.1%). Non-medical students outperformed medical students in OH awareness (64.1% vs. 45.2%, p < 0.001). The most important OH issues recognized by participants included OH major goal (86.6%), concept approach (83.5%), shared health threats by people, animal, and environment (82.1%). However, knowledge gaps were evident in awareness about Carbapenem-resistant Enterobacterales (65.3%), animal as an early warning sign of human illness (65%), zoonosis related to environmental toxicants. Key knowledge gaps were identified in awareness about Carbapenem-resistant Enterobacterales (65.3%), animal as an early warning sign of human illness (65%), zoonosis related to environmental toxicants. However, no specific knowledge gaps were identified related to impact of climate change on health. Conclusion While OH awareness among African students is relatively high, significant regional disparities and knowledge gaps remain, particularly in AMR and zoonotic disease prevention. Strengthening interdisciplinary education, enhancing regional OH initiatives, and incorporating OH into university curricula are crucial for fostering a well-informed future workforce.